Answer:
The answer is shown below
Explanation:
Let y(t) be the fraction of the population that has heard the rumor at time t and assume that the rate at which the rumor spreads is proportional to the product of the fraction y of the population that has heard the rumor and the fraction 1−y that has not yet heard the rumor.
a)
![(dy)/(dt)\ \alpha\ y(1-y)](https://img.qammunity.org/2021/formulas/mathematics/college/850k5448s6yjk30jb1516dw2v88giwmfvv.png)
where k is the constant of proportionality, dy/dt = rate at which the rumor spreads
b)
![(dy)/(dt)=ky(1-y)\\(dy)/(y(1-y))=kdt\\\int\limits {(dy)/(y(1-y))} \, =\int\limit {kdt}\\\int\limits {(dy)/(y)} +\int\limits {(dy)/(1-y)} =\int\limit {kdt}\\\\ln(y)-ln(1-y)=kt+c\\ln((y)/(1-y)) =kt+c\\taking \ exponential \ of\ both \ sides\\(y)/(1-y) =e^(kt+c)\\(y)/(1-y) =e^(kt)e^c\\let\ A=e^c\\(y)/(1-y) =Ae^(kt)\\y=(1-y)Ae^(kt)\\y=(Ae^(kt))/(1+Ae^(kt)) \\at \ t=0,y=10\%\\0.1=(Ae^(k*0))/(1+Ae^(k*0)) \\0.1=(A)/(1+A) \\A=(1)/(9) \\](https://img.qammunity.org/2021/formulas/mathematics/college/hpwhew2vjmlrhrtfljl5yrj2l2incr0v8z.png)
![y=((1)/(9) e^(kt))/(1+(1)/(9) e^(kt))\\y=(1)/(1+9e^(-kt))](https://img.qammunity.org/2021/formulas/mathematics/college/v71wdkz8gf9mkg7efmzkw1veub024m1j4k.png)
At t = 2, y = 40% = 0.4
c) At y = 75% = 0.75
![y=(1)/(1+9e^(-0.8959t))\\0.75=(1)/(1+9e^(-0.8959t))\\t=3.68\ days](https://img.qammunity.org/2021/formulas/mathematics/college/3kkkqqahq4tlcfx1y7tgvbixfn850u5gyj.png)